Evaluation of the CO2 tolerant cathode for solid oxide fuel cells: Praseodymium oxysulfates/Ba0.5Sr0.5Co0.8Fe0.2O3-δ - Yang, T.; Su, Chao; Wang, Wei; Meng, L.; Deng, J.; Liu, Yu; Rathore, S.; Shao, Zongping (Elsevier BV North-Holland, 2018)
An effective praseodymium oxysulfate/Ba0.5Sr0.5Co0.8Fe0.2O3-dcomposite cathode with high stability in 10% CO2/air was investigated. The addition of 50 vol.% of the praseodymium oxysulfate shows much better tolerance to CO2, and reduced the polarization resistance of the cathode to 1/3 comparing with that of Ba0.5Sr0.5Co0.8Fe0.2O3-d(BSCF). The CO2–temperature programmed desorption (TPD) and the electrochemical impedance spectroscopy (EIS) proved the effectiveness of the praseodymium oxysulfate phase to reduce the electrode resistance and to improve the CO2resistance. The coefficient thermal expansion (CTE) rate along with the different volume percentage of praseodymium oxysulfate was also measured and it was found that the praseodymium oxysulfate helps to regulate the total CTE of the composite to match with doped-ceria electrolyte. It is proposed the higher acidity of Pr3+/4+cations inhibited the reaction of alkaline earth metal oxide to form carbonates on the surface of the BSCF particles. The above results proved praseodymium oxysulfate/Ba0.5Sr0.5Co0.8Fe0.2O3-dto be a highly active and stable cathode for solid oxide fuel cells.